ABOUT THE ANALYSIS OF THE WORK " GAROV" - Yodgorova Nastarin Hamzayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article is mainly about the etymology of the word "garov" and its meanings. At the same time, the origin of the word "garov" and its negative consequences today are explained in detail based on examples and analysis of works.